Answer:
[tex]y=A+Bx^{2}[/tex]
Step-by-step explanation:
The given Cauchy-Euler equation is: [tex]x^2y''-xy'=0[/tex]
Comparing to the general form: [tex]ax^2y''+bxy'+cy=0[/tex], we have a=1,b=-1 and c=0
The auxiliary solution is given by: [tex]am(m-1)+bm+c=0[/tex]
[tex]\implies m(m-1)-m=0[/tex]
[tex]\implies m(m-1-1)=0[/tex]
[tex]\implies m(m-2)=0[/tex]
[tex]\implies m=0\:\:or\:\:m=2[/tex]
The general solution to this is of the form [tex]y=Ax^{m_1}+Bx^{m_2}[/tex], where A and B are constants.
[tex]y=Ax^{0}+Bx^{2}[/tex]
Therefore the general solution is;
[tex]y=A+Bx^{2}[/tex]
Let [tex]y_1=A[/tex] and [tex]y_2=Bx^2[/tex]
Since we CANNOT express the two solutions as constant multiple of each other, we say the two solutions are linearly independent.
[tex]y_1\neCy_2[/tex], where C is a constant.